Life Cycle Assessment in the Agri-food Sector : Case Studies, Methodological Issues and Best Practices - Notarnicola, Bruno; Salomone, Roberta; Petti, Luigia; Renzulli, Pietro A.; Roma, Rocco; Cerutti, Alessandro K. (Springer International Publishing : Imprint: Springer, 2015)
This book examines environmental hotspots, methodological issues and best practices for the agri-food sector from a life cycle perspective. The aim is to create practical guidelines for the LCA community and the main actors of the agro-food chains: farmers, manufacturing companies, consumers and others. The book is focused on some of the most relevant and productive agri-food supply chains, including olive oil, wine, cereals and derived products, meats, dairy products and fruit. The first chapter introduces key concerns, applications, and methodological uncertainties of the application of life cycle assessment (LCA) principles and practices to the agri-food sector, offering an overview of the main dietary issues, which acknowledges the importance of consumer behaviour. Chapter 2 focuses on the olive oil industry, an economically significant sector. The authors undertake a review of international LCA implementation, a description of LCA implementation problems and application guidelines. The third chapter surveys the wine sector, offering a critical review of existing LCA methodologies and case studies, and a description of scientifically sound environmental improvements suggested by published LCAs. Chapter 4 covers the principal cereal and derived products, presents conclusions and describes the main hot spots in the cereal supply chain. Chapter 5 explores livestock and derived edible products, a sector which has an important economical role and which is associated with adverse environmental effects, covering LCA implementations, methodological problems and best practices. The final chapter focuses on fruit products, among the less environmentally damaging foods in western diets. After an overview of the European fruit industry, the authors discuss methodological problems concerned with the application of LCA to the sector and propose practical guidelines.